Kesuma Enterprise / Kalsom Yahaya ... [et al.] - Yahaya, Kalsom; Ismail, Siti Fatimah; Samad, Hisyam; Mohammad, Zainurib (Faculty of Computer and Mathematical Sciences, 2003)
Uniform are often used as uniformity for a government and company. Besides that it also helps to dhow the identity of a government and company. Since there is few of bumiputras involve in the business and still far behind, we trying to explore this few field of business and try to open wide the scope of this business in Malaysia. We decided to name our business as KESUMA ENTERPRISE, suitable with the product that we produced and supply that is uniforms. We reached a consensus to form thus business as partnership. Under all of the rules and regulation we believe thus is the best way to run up our business.